MENINGKATKAN KETERAMPILAN BERBAHASA ARAB SANTRI MELALUI METODE MUHADATSAH DI PONDOK PESANTREN KMI AR RASYID - Ibnu Rizqulloh; Nafiah Nur Isti Qoma, Ashri; Iqbal Al Fatih, Muhammad Iqbal Al Fatih; Ali Mustofa , Triono (LPPM STAIMAS WONOGIRI, 2025)
This study aims to analyze the implementation of the Muhadatsah method and its influence on students’ Arabic language proficiency at KMI Ar-Rasyid Islamic Boarding School in Wonogiri. The research originates from the growing need within Islamic boarding schools to improve the effectiveness of Arabic instruction through a communicative approach that emphasizes active conversational practice. Employing a descriptive qualitative approach through field research, the data were obtained from in-depth interviews, participant observation, and documentation of Muhadatsah activities. The data were analyzed using the Miles and Huberman model, encompassing data reduction, presentation, and verification. The results indicate that the Muhadatsah method significantly contributes to improving students’ speaking and listening skills, expanding their vocabulary, and fostering self-confidence in communicating in Arabic. The implementation also succeeded in creating an interactive and contextual learning environment, despite challenges such as time limitations, varying language proficiency among students, and the need for consistent supervision. Theoretically, this study reinforces the relevance of communicative approaches in Arabic language education within Islamic boarding schools, while practically providing recommendations for Islamic educational institutions to integrate Muhadatsah activities sustainably within their language curriculum. The findings are expected to serve as a foundation for future studies exploring the effectiveness of the Muhadatsah method in modern Arabic language pedagogy.